Polymer and resin composition for optical lens
By using polynaphthalene-sulfide-based resin and specific synthesis methods, the shortcomings of high-refractive index materials in the prior art in lens moldability are solved, and a resin composition for optical lens with high refractive index and excellent lens moldability are realized. Manufacturing of micro lenses.
Patent Information
- Application Number
- CN202380040741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-03
- Filing Date
- 2023-03-24
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, although there is a polymer material with a high refractive index, it is not necessarily a suitable material from the viewpoint of lens moldability, and it is difficult to achieve both high refractive index and excellent lens moldability.
The polymer is synthesized by an oxidation polymerization method using a polynaphthalene-sulfide-based resin, and combined with a specific structural unit ratio and an organic solvent to form an optical lens resin composition with high refractive index and excellent lens moldability.
A high refractive index of 1.75 or above is achieved at a wavelength of 550 nm, and a microlens with narrow gaps between adjacent lenses are formed by the etchback method, which significantly improves the lens moldability.
Smart Images

Figure CN119452019A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer, a resin composition for an optical lens, and a microlens obtained from the resin composition. Background Art
[0002] In recent years, in the field of electronic devices such as liquid crystal displays, organic EL displays, light-emitting diodes, solar cells, and CCD / CMOS image sensors, resin compositions using polymer materials having a high refractive index are often used for optical components such as protective films, planarization films, insulating films, anti-reflection films, refractive index control films, microlenses, in-layer lenses, optical waveguides, and film substrates. For example, by applying high refractive index materials to microlenses for CCD / CMOS image sensors, it is expected that sensor performance will be improved.
[0003] As one of the methods for manufacturing microlenses for CCD / CMOS image sensors, an etch-back method is known (Patent Documents 1 and 2). That is, a resist pattern is formed on a microlens resin layer formed on a color filter layer, and the resist pattern is reflowed by heat treatment to form a lens pattern. The lens pattern formed by reflowing the resist pattern is used as an etching mask, and the underlying microlens resin layer is etched back to transfer the lens pattern shape to the microlens resin layer, thereby manufacturing a microlens.
[0004] In the etch-back method, the lens moldability based on dry etching is important. For example, when transferring the lens pattern shape to the underlying microlens resin layer, the dry etching rate X of the lens pattern needs to be equal to the dry etching rate Y of the microlens resin layer (X:Y=1:0.8~1.2) (Patent Document 3). In addition, in order to improve the light collection efficiency, it is desired that the gap between adjacent microlenses is narrow. That is, a material is required in which the width of the microlens formed after dry etching is larger than the width of the lens pattern before dry etching. Such lens moldability depends largely on the material of the microlens resin layer.
[0005] On the other hand, as a means of increasing the refractive index of a polymer material, it is known to introduce an aromatic ring, a halogen atom other than a fluorine atom, a sulfur atom, a metal atom, or a hydrogen bond, etc. into the molecule of the polymer material. For example, polyphenylene sulfide having a phenolic hydroxyl group has recently been found to be a polymer material having a high refractive index by utilizing the effects of the introduction of an aromatic ring, a sulfur atom, and a hydrogen bond (Patent Document 4 and Non-Patent Document 1).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 1-10666
[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 6-112459
[0010] Patent Document 3: International Publication No. 2013 / 005619
[0011] Patent Document 4: International Publication No. 2022 / 065381
[0012] Patent Document 5: Japanese Patent Application Publication No. 2015-168790
[0013] Patent Document 6: Japanese Patent Application Publication No. 2017-52834
[0014] Non-patent literature
[0015] Non-patent literature 1: Macromolecules, 2022, 55, 6, 2252-2259 Summary of the invention
[0016] Problems to be solved by the invention
[0017] However, the inventors conducted experiments and found that although polyphenylene sulfide having a phenolic hydroxyl group does have a high refractive index, it is not necessarily a suitable material from the viewpoint of lens moldability. It is desired to develop a material that exhibits a high refractive index and excellent lens moldability.
[0018] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a polymer and a resin composition having both a high refractive index and excellent lens moldability.
[0019] Means for solving problems
[0020] The present inventors have conducted intensive studies to solve the above-mentioned problems and, as a result, have found that the above-mentioned problems can be solved by using a polynaphthalene sulfide-based resin, thereby completing the present invention.
[0021] That is, the present invention provides the following [1] to
[11] .
[0022] [1] A polymer comprising a structural unit represented by the following formula (1), wherein the structural unit does not include a structural unit represented by the following formula (1a),
[0023] [Chemistry 1]
[0024]
[0025] In the formula, X independently represents a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group, and n represents an integer of 1 to 6.
[0026] [Chemistry 2]
[0027]
[0028] [2] The polymer according to [1], wherein in the structural unit represented by the formula (1), n represents 1.
[0029] [3] The polymer according to [1] or [2], wherein in the structural unit represented by the formula (1), X represents a methyl group or an ethyl group.
[0030] [4] The polymer according to [1] or [2], wherein in the structural unit represented by the formula (1), X represents a methoxy group or an ethoxy group.
[0031] [5] The polymer according to [1] or [2], wherein in the structural unit represented by the formula (1), X represents a hydroxyl group.
[0032] [6] The method for producing a polymer according to [1] or [2], which is a method for producing a polymer containing a structural unit represented by the formula (1), the method comprising: subjecting a disulfide monomer represented by the following formula (2) and / or a thiol monomer represented by the following formula (3) to oxidative polymerization, wherein the disulfide monomer does not include a disulfide monomer represented by the following formula (2a), and the thiol monomer does not include a thiol monomer represented by the following formula (3a),
[0033] [Chemistry 3]
[0034]
[0035] In the formula, X and n have the same definitions as in formula (1),
[0036] [Chemistry 4]
[0037]
[0038] [7] A resin composition for an optical lens, comprising: (A) the polymer according to [1] or [2] and / or a polymer containing a structural unit represented by the following formula (4) and (B) an organic solvent,
[0039] [Chemistry 5]
[0040]
[0041] [8] The resin composition for an optical lens according to [7], wherein the component (B) contains at least one organic solvent selected from the group consisting of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, ethyl lactate, n-butyl lactate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, 2-heptanone, cyclopentanone, cyclohexanone, γ-butyrolactone, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.
[0042] [9] The resin composition for an optical lens according to [7], further comprising (C) a polyfunctional epoxy compound.
[0043]
[10] The resin composition for an optical lens according to [7], which is used for producing a microlens.
[0044]
[11] A microlens obtained from the resin composition for an optical lens according to
[10] .
[0045] Effects of the Invention
[0046] According to the present invention, a resin film containing a polynaphthalene sulfide-based resin shows a high refractive index of 1.75 or more at a wavelength of 550 nm, and microlenses having a narrow gap between adjacent lenses can be formed by an etch-back method. DETAILED DESCRIPTION
[0047] The polymer and the resin composition for optical lens of the present invention are described in more detail below. The resin composition for optical lens of the present invention is characterized in that it contains the component (A) and the component (B) described below. It should be noted that in the following description, the so-called solid content means the components other than the solvent constituting the resin composition.
[0048] [polymer]
[0049] The polymer of the present invention is not particularly limited as long as it is a polymer including a structural unit represented by the following formula (1) (but excluding a structural unit represented by the following formula (1a)).
[0050] [Chemistry 6]
[0051]
[0052] (In the formula, X independently represents a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group, and n represents an integer of 1 to 6.)
[0053] [Chemistry 7]
[0054]
[0055] Examples of the structural units of the polymer include structural units represented by the following formulae (1ba) to (1bn), (1ca) to (1cn), (1da) to (1dn), (1ea) to (1en), and (1fn) to (1fn).
[0056] [Chemistry 8]
[0057]
[0058] [Chemistry 9]
[0059]
[0060] (In the formula, OMe represents a methoxy group.)
[0061] [Chemistry 10]
[0062]
[0063] (Wherein, OEt represents ethoxy.)
[0064] [Chemistry 11]
[0065]
[0066] (In the formula, Me represents a methyl group.)
[0067] [Chemistry 12]
[0068]
[0069] (In the formula, Et represents ethyl.)
[0070] The proportion of the structural unit represented by the above formula (1) in the above polymer (excluding the structural unit represented by the above formula (1a)) is preferably 10 mol% or more, more preferably 30 mol% or more, further preferably 50 mol% or more, and further preferably 80 mol% or more. By making the proportion of the structural unit within the above range, it is possible to produce a microlens with a narrower gap between adjacent lenses.
[0071] In the above formula (1), X represents methyl, ethyl, methoxy, ethoxy or hydroxy, and methyl, methoxy and hydroxy are preferred. From the viewpoint of improving solubility in organic solvents and improving refractive index, hydroxy is particularly preferred. In addition, from the viewpoint of easy synthesis, n in the above formula (1) is preferably 1.
[0072] The molecular weight of the polymer is preferably 500 to 100,000, more preferably 1,000 to 30,000, and even more preferably 1,000 to 10,000, as represented by a polystyrene-equivalent weight average molecular weight calculated by gel permeation chromatography (GPC).
[0073] The above polymer can be synthesized, for example, by applying various known polyarylene sulfide production methods to naphthalene derivatives (polycondensation of aromatic halogen compounds and sodium sulfide, oxidative polymerization of aromatic thiol compounds or aromatic disulfide compounds, etc.). The polymer having a hydroxyl group can be synthesized by applying various known polyarylene sulfide production methods to naphthol derivatives having protected hydroxyl groups, and then deprotecting part or all of the protecting groups.
[0074] As a method for producing the above-mentioned polymer, an oxidative polymerization method is preferred. In particular, if it is possible to produce at room temperature and pressure without using a metal catalyst, it is preferred to use the oxidative polymerization method using a quinone-based oxidant and an acid as described in Patent Documents 5 and 6. As a specific method for producing the above-mentioned polymer, there can be cited a method of using an aromatic thiol compound containing a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group, or an aromatic disulfide compound containing a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group as a monomer, and performing oxidative polymerization using a quinone-based oxidant and an acid; a method of using an aromatic thiol compound containing a protected hydroxyl group or an aromatic disulfide compound containing a protected hydroxyl group as a monomer, and performing oxidative polymerization using a quinone-based oxidant and an acid, and then deprotecting part or all of the protecting group. As for the protected hydroxyl group, there is no particular limitation as long as the polymerization proceeds. From the perspective of stability that does not interfere with the quinone-based oxidant and acid, an alkoxy group is preferred, and a methoxy group or an ethoxy group is more preferred. In the case of a methoxy group, it is particularly preferred because the deprotection reaction can be more easily performed. The alkoxy group can be converted to a hydroxyl group by removing the alkyl group by the action of an acid. Examples of the acid include Lewis acids such as trisubstituted boron compounds (boron tribromide, etc.) and aluminum chloride, and Bronsted acids such as thiol compounds (dodecanethiol, etc.) and hydrogen bromide. The acid is not particularly limited as long as it can be converted to a hydroxyl group. The protecting group may be completely deprotected or partially left. By appropriately adjusting the deprotection rate, the optical properties and solubility can be controlled.
[0075] When the oxidative polymerization method is used, a disulfide monomer represented by the above formula (2) (excluding the disulfide monomer represented by the above formula (2a)) and / or a thiol monomer represented by the above formula (3) (excluding the thiol monomer represented by the above formula (3a)) can be preferably used.
[0076] The monomer used in the synthesis of the above-mentioned polymer can be used alone or in combination of two or more. From the viewpoints of adjusting optical properties and solubility in organic solvents, as required, a disulfide monomer not represented by the above-mentioned formula (2) or a thiol monomer not represented by the above-mentioned formula (3) can be used. That is, the polymer can be a homopolymer or a copolymer as long as it contains at least one structural unit represented by the above-mentioned formula (1). In the case where the polymer is a copolymer, its repeating structure is not particularly limited, and it can be any of an alternating copolymer, a block copolymer, a gradient copolymer and a random copolymer. In addition, the polymer can be branched according to the polymerization conditions.
[0077] [(A) ingredient]
[0078] The component (A) is not particularly limited as long as it is a polymer containing a structural unit represented by the above formula (1) (wherein, the structural unit represented by the above formula (1a) is not included) and / or a polymer containing a structural unit represented by the above formula (4). In addition, other structural units other than the structural unit represented by the above formula (1) and the structural unit represented by the above formula (4) may be included within the scope of not impairing the effect of the present invention. As other structural units, for example, structural units represented by the following formulas (5) to (17) can be listed.
[0079] [Chemistry 13]
[0080]
[0081] (In the formula, OMe represents a methoxy group.)
[0082] The proportion of the structural unit represented by the above formula (1) (excluding the structural unit represented by the above formula (1a)) and / or the structural unit represented by the above formula (4) in the component (A) is preferably 10 mol% or more, more preferably 30 mol% or more, further preferably 50 mol% or more, and further preferably 80 mol% or more. By making the proportion of the structural unit within the above range, a microlens with a narrower gap between adjacent lenses can be produced.
[0083] The structural unit represented by the above formula (1) has reduced crystallinity due to the presence of a substituent, and is therefore superior to the structural unit represented by the above formula (4) from the viewpoint of solubility in organic solvents. X in the above formula (1) represents a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group, wherein a methyl group, a methoxy group or a hydroxyl group is preferred, and a hydroxyl group is particularly preferred from the viewpoint of improving solubility in organic solvents and improving the refractive index. In addition, from the viewpoint of ease of synthesis, n in the above formula (1) is preferably 1.
[0084] The molecular weight of the component (A) is preferably 500 to 100,000, more preferably 1,000 to 30,000, and even more preferably 1,000 to 10,000, as represented by a polystyrene-equivalent weight average molecular weight calculated by gel permeation chromatography (GPC).
[0085] The component (A) can be synthesized, for example, by applying various known methods for producing polyarylene sulfide to a naphthalene derivative (polycondensation of an aromatic halogen compound and sodium sulfide, oxidative polymerization of an aromatic thiol compound or an aromatic disulfide compound, etc.). The polymer having a hydroxyl group can be synthesized by applying various known methods for producing polyarylene sulfide to a naphthol derivative having a protected hydroxyl group, and then deprotecting part or all of the protecting group.
[0086] As the method for producing the component (A), an oxidative polymerization method is preferred. In particular, if it is possible to produce at room temperature and pressure without using a metal catalyst, the oxidative polymerization method using a quinone-based oxidant and an acid as described in Patent Documents 5 and 6 is preferably used. As a specific method for producing the component (A), there can be cited a method of using an aromatic thiol compound that may contain a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group, or an aromatic disulfide compound that may contain a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group as a monomer, and performing oxidative polymerization using a quinone-based oxidant and an acid; a method of using an aromatic thiol compound containing a protected hydroxyl group or an aromatic disulfide compound containing a protected hydroxyl group as a monomer, and performing oxidative polymerization using a quinone-based oxidant and an acid, and then deprotecting part or all of the protecting groups. As for the protected hydroxyl group, there is no particular limitation as long as the polymerization proceeds. From the perspective of stability that does not interfere with the quinone-based oxidant and acid, an alkoxy group is preferred, and a methoxy group or an ethoxy group is more preferred. In the case of a methoxy group, it is particularly preferred because the deprotection reaction can be more easily performed. The alkoxy group can be converted to a hydroxyl group by removing the alkyl group by the action of an acid. Examples of the acid include Lewis acids such as trisubstituted boron compounds (boron tribromide, etc.) and aluminum chloride, and Bronsted acids such as thiol compounds (dodecanethiol, etc.) and hydrogen bromide. The acid is not particularly limited as long as it can be converted to a hydroxyl group. The protecting group may be completely deprotected or partially left. By appropriately adjusting the deprotection rate, the optical properties and solubility can be controlled.
[0087] In the case of synthesizing a polymer containing a structural unit represented by the above formula (1) (excluding a structural unit represented by the above formula (1a)) by an oxidative polymerization method, a disulfide monomer represented by the above formula (2) (excluding a disulfide monomer represented by the above formula (2a)) and / or a thiol monomer represented by the above formula (3) (excluding a thiol monomer represented by the above formula (3a)) can be preferably used. In addition, in the case of synthesizing a polymer containing a structural unit represented by the above formula (4) by an oxidative polymerization method, a disulfide monomer represented by the following formula (18) and / or a thiol monomer represented by the following formula (19) can be preferably used.
[0088] [Chemistry 14]
[0089]
[0090] The monomers used in the synthesis of component (A) may be used alone or in combination of two or more. From the viewpoint of adjusting optical properties, solubility in organic solvents, etc., disulfide monomers not represented by the above formula (2) and the above formula (18) (for example, disulfide monomers represented by the following formulas (20) to (38) can be used as needed.) Or thiol monomers not represented by the above formula (3) and the above formula (19) (for example, thiol monomers represented by the following formulas (39) to (57) can be used.). That is, as long as the polymer contains at least one structural unit represented by the above formula (1) or the above formula (4), it can be a homopolymer or a copolymer. In the case where the polymer is a copolymer, there is no particular limitation on its repeating structure, and it can be any of an alternating copolymer, a block copolymer, a gradient copolymer and a random copolymer. In addition, the polymer can be branched depending on the polymerization conditions.
[0091] [Chemistry 15]
[0092]
[0093] (In the formula, OMe represents a methoxy group.)
[0094] [Chemistry 16]
[0095]
[0096] (In the formula, OMe represents a methoxy group.)
[0097] [(B) ingredient]
[0098] The component (B) is not particularly limited as long as it is an organic solvent that dissolves the component (A), and an organic solvent having a melting point of 15°C or less and a boiling point of 85°C or more is preferred. The melting point and boiling point refer to the melting point and boiling point under 1 atmosphere. The resin composition has excellent handling properties at room temperature due to the melting point being 15°C or less. From the perspective of storage properties in a cold place, the melting point is preferably 10°C or less, and more preferably 5°C or less. In addition, the lower limit of the melting point is not particularly limited, and for example, it is preferably -150°C or more. On the other hand, the coating formed by applying the resin composition on the substrate becomes difficult to whiten due to the boiling point being 85°C or more. From the perspective of easily forming a particularly homogeneous coating, the boiling point is preferably 100°C or more, and more preferably 115°C or more. In addition, from the perspective of organic solvent removability, the upper limit of the boiling point is preferably 300°C or less, more preferably 250°C or less, and further preferably 220°C or less.
[0099] Specific examples of the component (B) include methylcyclohexane, ethylcyclohexane, n-heptane, toluene, o-xylene, m-xylene, mesitylene, chlorobenzene, o-dichlorobenzene, m-dichlorobenzene, anisole, phenethyl ether, di-n-propyl ether, di-n-butyl ether, diisobutyl ether, di-n-pentyl ether, diisopentyl ether, di-n-hexyl ether, n-butyl ethyl ether, methyl n-pentyl ether, cyclopentyl methyl ether, tetrahydropyran, 1,3-dioxane, 1,4-dioxane, 1-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, 1-pentanol, 2-pentanol, 3-pentanol, cyclopentanol, benzyl alcohol, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ... Ethyl alcohol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, triethylene glycol monomethyl ether, triethylene glycol dimethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, n-butyl formate, isobutyl formate, n-pentyl formate, isopentyl formate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, tert-butyl acetate, n-pentyl acetate, isopentyl acetate, n-hexyl acetate, isohexyl acetate, n-heptyl acetate, isoheptyl acetate, n-octyl acetate, Isooctyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, propylene glycol diacetate, triacetin, ethyl propionate, n-propyl propionate, isopropyl propionate, n-butyl propionate, isobutyl propionate, tert-butyl propionate, propylene glycol monomethyl ether propionate, methyl butyrate, ethyl butyrate, n-propyl butyrate, isopropyl butyrate, n-butyl butyrate, isobutyl butyrate, tert-butyl butyrate, methyl isobutyrate, ethyl isobutyrate, n-propyl isobutyrate, Isopropyl isobutyrate, n-butyl isobutyrate, isobutyl isobutyrate, tert-butyl isobutyrate, methyl lactate, ethyl lactate, n-propyl lactate, isopropyl lactate, n-butyl lactate, isobutyl lactate, tert-butyl lactate, methyl acetoacetate, ethyl acetoacetate, n-propyl acetoacetate, isopropyl acetoacetate, n-butyl acetoacetate, isobutyl acetoacetate, tert-butyl acetoacetate, dimethyl malonate, diethyl malonate, methyl glycolate, ethyl glycolate, methyl pyruvate, ethyl pyruvate, ethyl ethoxyacetate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, dimethyl carbonate, diethyl carbonate, 2-pentanone, 3-pentanone, cyclopentanone, 2,4-pentanedione, 4-methyl-2-pentanone, 4-hydroxy-4-methyl-2-pentanone, 2-hexanone, 3-hexanone, 3-methyl-2-hexanone, 5-methyl-2-hexanone, 2-methyl-3-hexanone, 5-methyl-3-hexanone, cyclohexanone, 2-methylcyclohexanone, 3-methylcyclohexanone, 4-methylcyclohexanone, 2-heptanone, 3-heptanone, 4-heptanone, 2-methyl-3-heptanone, 5-methyl- 3-heptanone, 2,6-dimethyl-4-heptanone, cycloheptanone, γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, ε-caprolactone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylisobutyramide, N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone, etc.
[0100] As the component (B), from the viewpoint of improving the leveling property of a coating film formed by applying the resin composition on a substrate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, ethyl lactate, n-butyl lactate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, 2-heptanone, cyclopentanone, cyclohexanone, γ-butyrolactone, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone are preferred. In consideration of the solubility of the component (A), cyclopentanone and γ-butyrolactone are particularly preferred.
[0101] The above-mentioned (B) component can be used alone or in combination of two or more. In addition, it can be appropriately mixed with a solvent other than the (B) component. In this case, the content of the (B) component is preferably 50% to 100% by mass of the overall solvent containing the (B) component and other solvents, more preferably 60% to 100% by mass, and further preferably 70% to 100% by mass.
[0102] Specific examples of the other solvents include methanol, ethanol, 2-propanol, dichloromethane, 1,2-dichloroethane, chloroform, acetone, 2-butanone, dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), ethyl acetate, and acetonitrile.
[0103] [(C) Polyfunctional epoxy compound]
[0104] The resin composition of the present invention may further contain (C) a polyfunctional epoxy compound for the purpose of improving chemical resistance. The component (C) is not particularly limited as long as it is a compound having at least two oxirane rings in the molecule, and for example, the following commercial products and compounds can be used.
[0105] TEPIC (registered trademark) -G, -L, -VL, -S, -SP, -SS, -HP (all manufactured by Nissan Chemical Co., Ltd.), Marproof (registered trademark) G-01100, G-0105SA, G-0130SF, G-0130SP, G-0150M, G-0250SF, G-0250SP, G-05100, G-2050M, G-017581 (all manufactured by NOF Corporation), OGSOL (registered trademark) PG-100, CG-500, EG-200, EG-280 (all manufactured by Osaka Gas Chemicals Co., Ltd.), GTR-1800 (all manufactured by Nippon Kayaku Co., Ltd.), EPICLON (registered trademark) 830, 830-S, 835, 840, 840-S, 850, 850-S, 850-LC, HP-820 (all manufactured by DIC Corporation), DENACOL (registered trademark) EX-201, EX-211, EX-212, EX-252, EX-810, EX-811 , EX-821, EX-830, EX-832, EX-841, EX-850, EX-851, EX-861, EX-920, EX-931, EX-991L, EX-313, EX-3 14. EX-321, EX-321L, EX-411, EX-421, EX-512, EX-521, EX-612, EX-614, EX-614B, EX-622 (the above is NagaseChemteX (manufactured by Mitsubishi Chemical Corporation), jER (registered trademark) 152, 604, 630, 806, 806H, 807, 825, 827, 828, 828EL, 828US, 828XA, 834, 890, 1031S, 1032H60, 1750, YL980, YL983U, YL6121HA, YL6677, YL6810, YX4000, YX4000H, YX4000HS, YX7700, YX8000, YX8034, YX8800 (all manufactured by Mitsubishi Chemical Corporation), TETRAD (registered trademark) -C, -X (all manufactured by Mitsubishi Gas Chemical Corporation), CELLOXIDE (registered trademark) 2021P, 2081 、EPOLEAD (registered trademark) GT401、EHPE (registered trademark) 3150、3150CE (all manufactured by DAICEL Co., Ltd.), EPOTOHTO (registered trademark) YD-115、YD-115CA、YD-127、YD-128、YD-128G、YD-128S、YD-128CA、YD-8125、YD-825GS、YDF-170、YDF-170N、YDF-8170C、YDF-870GS、ZX-1059、YH-404、YH-434、YH-434L、YH-513、YH-523、ST-3000 (all manufactured by NIPPON STEEL CHEMICAL & MATERIAL CO., LTD.), ADEKA RESIN (registered trademark) EP-4100, EP-4100G, EP-4100E, EP-4100TX, EP-4300E, EP-4100, EP-4400, EP-4520S, EP-4530, EP-4901, EP-4901E, EP-4000, EP-4005, EP-7001, EP-4080E, EPU-6, EPU-7N, EPU-11F, EPU-15F, EPU-1395, EPU-73B, EPU-17, EPU-17T-6, EPR-1415-1, EPR-2000, EPR-2007, Adeka Glycirol (registered trademark) ED-503, ED-503G, ED-506, ED-523T, ED-505 (all manufactured by ADEKA Corporation), Sumi-Epoxy (registered trademark) ELM-434, ELM-434L, ELM-434VL, ELM-100, ELM-100H (all manufactured by Sumitomo Chemical Co., Ltd.), EpolightMultifunctional epoxy resins such as M-1230, 40E, 100E, 200E, 400E, 70P, 200P, 400P, 1500NP, 1600, 80MF, 4000, 3002(N) (all manufactured by Kyoeisha Chemical Co., Ltd.) and THI-DE (manufactured by ENEOS Co., Ltd.).
[0106] The above-mentioned (C) component can be used alone or in combination of two or more. When the resin composition of the present invention includes the (C) component, the content of the (C) component is preferably 5 to 50 parts by mass, and more preferably 10 to 30 parts by mass relative to 100 parts by mass of the (A) component. By making the content of the (C) component within the above range, the chemical resistance can be further improved without damaging the refractive index.
[0107] [Surfactant]
[0108] The resin composition of the present invention may also optionally contain a surfactant for the purpose of improving coating properties. Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene / polyoxypropylene block copolymers; sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan monooleate. Sorbitan fatty acid esters such as polyoxyethylene sorbitan tristearate; nonionic surfactants such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate; EFTOP (registered trademark) EF301, EF303, EF352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) ), MEGAFAC (registered trademark) F-171, F-173, R-30, R-40, R-40-LM (all manufactured by DIC Corporation), Fluorad FC430, FC431 (all manufactured by Sumitomo 3M Corporation), AsahiGuard (registered trademark) AG710, SURFLON (registered trademark) S-382, SC101, SC102, SC103, SC104, SC105, Fluorine-based surfactants such as FTERGENT series (manufactured by NEOS Co., Ltd.), such as SC106 (manufactured by AGC Co., Ltd.), FTX-206D, FTX-212D, FTX-218, FTX-220D, FTX-230D, FTX-240D, FTX-212P, FTX-220P, FTX-228P, and FTX-240G, and organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.). These surfactants may be used alone or in combination of two or more.
[0109] When the resin composition of the present invention contains a surfactant, the content of the surfactant is preferably 0.001 to 3 parts by mass, more preferably 0.005 to 1 part by mass, and even more preferably 0.01 to 0.5 parts by mass, based on 100 parts by mass of the total solid content.
[0110] [Other additives]
[0111] The resin composition of the present invention may further contain additives such as a curing aid, an antioxidant, a light stabilizer (HALS), an ultraviolet absorber, a plasticizer, and an adhesion promoter as necessary, unless the effects of the present invention are impaired.
[0112] [Method for preparing resin composition]
[0113] The preparation method of the resin combination of the present invention is not particularly limited, for example, the method of mixing (A) component and (B) component, and then optionally (C) component, other components, and making a uniform solution can be listed. In addition, as required, the obtained solution can be filtered using a filter with a pore size of 0.1 μm to 10 μm. The solid content concentration of the resin combination obtained in this way is usually 1% by mass to 50% by mass from the viewpoint of the coating property of the substrate.
[0114] [Method for producing resin film]
[0115] On a substrate (e.g., a PET film, a TAC film, a semiconductor substrate, a glass substrate, a quartz substrate, a silicon wafer, and a substrate having various metal films or color filters formed on their surfaces), the resin composition of the present invention is applied by an appropriate coating method such as a spin coater or a coater, and then baked using a heating means such as a hot plate or an oven to prepare a resin film. As for the baking conditions, a baking temperature of 50°C to 300°C and a baking time of 0.1 minute to 360 minutes are appropriately selected. The baking when preparing the above-mentioned resin film can be processed in two or more stages. The film thickness of the formed resin film is 0.001μm to 1000μm, preferably 0.01μm to 100μm, and more preferably 0.1μm to 10μm.
[0116] [Method for producing microlenses]
[0117] A resist is applied to a resin film produced by the above-mentioned [method for producing a resin film], and the resist is exposed through a predetermined mask. If necessary, post-exposure heating (PEB) is performed, and then alkali development, rinsing and drying are performed to form a resist pattern on the resin film. As exposure light, for example, g-rays, i-rays, KrF excimer lasers and ArF excimer lasers can be used. Next, the resist pattern is reflowed by performing a heat treatment to form a lens pattern. Using the lens pattern as an etching mask, the resin film under the lens pattern is etched back, and the shape of the lens pattern is transferred to the resin film, thereby producing a microlens. In this method, when transferring the shape of the lens pattern to the resin film under the layer (resin layer for microlenses), it is necessary to make the dry etching rate X of the resist pattern equal to the dry etching rate Y of the resin layer for microlenses (X:Y=1:0.8~1.2).
[0118] Example
[0119] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0120] [Measurement of Polystyrene Equivalent Weight Average Molecular Weight of Polymer]
[0121] Equipment: GPC system manufactured by JASCO Corporation
[0122] Column: Shodex (registered trademark) KF-804L and KF-803L
[0123] Column oven: 40°C
[0124] Flow rate: 1mL / min
[0125] Eluent: Tetrahydrofuran
[0126] Sample concentration: 10mg / mL
[0127] Sample injection volume: 20μL
[0128] Standard material: monodisperse polystyrene
[0129] Detector: Differential Refractometer
[0130] [Manufacturing of monomers]
[0131] <Monomer Synthesis Example 1>
[0132] In a flask equipped with a stirrer, 44.4 g of 2-methoxynaphthalene, 800 mL of tetrahydrofuran, and 184 mL of a hexane solution of n-butyl lithium (1.6 mol / L) were added in sequence under an ice bath. After stirring for 1 hour, the mixture was cooled to 80°C below freezing point and 9.0 g of sulfur was added. Then, the mixture was stirred at room temperature for 20 hours and separated with a saturated aqueous ammonium chloride solution. The obtained organic layer was dehydrated with sodium sulfate, filtered, and the filtrate was evaporated to obtain 53.5 g of 2-methoxy-1-naphthol as a yellow-green solid.
[0133] Next, 53.5 g of the obtained 2-methoxy-1-naphthol and 500 mL of chloroform were placed in a flask equipped with a stirrer, and a solution prepared by dissolving 35.7 g of iodine in 250 mL of methanol was added dropwise, and stirred at room temperature for 20 hours. Next, 1 M hydrochloric acid, 1 M sodium hydroxide aqueous solution, and brine were used for separation treatment in sequence, and the obtained organic layer was dehydrated with sodium sulfate, filtered, and the filtrate was evaporated to obtain a yellow oil. After dissolving the oil in 200 mL of chloroform, 200 mL of methanol was added to crystallize it, and the obtained solid was dried at 50° C. for 3 hours under reduced pressure to obtain a white solid monomer [bis(2-methoxynaphthyl) disulfide].
[0134] <Monomer Synthesis Example 2>
[0135] In a flask equipped with a stirrer, 22.4 g of 2-methoxythiophenol and 300 mL of chloroform were placed, and then a solution prepared by dissolving 20.7 g of iodine in 150 mL of methanol was added dropwise, and the mixture was stirred at room temperature for 1 hour. Next, 20 mL of a 1N sodium thiosulfate aqueous solution was added to remove the remaining iodine, and then the mixture was separated with 1M hydrochloric acid, 1M sodium hydroxide aqueous solution, and saline in sequence, and the obtained organic layer was dehydrated with sodium sulfate, filtered, and the filtrate was evaporated to obtain a pale yellow solid monomer [bis(2-methoxyphenyl) disulfide].
[0136] <Monomer Synthesis Example 3>
[0137] In a flask equipped with a stirrer, 25.0 g of 2-naphthol and 300 mL of chloroform were placed, and then a solution prepared by dissolving 20.2 g of iodine in 150 mL of methanol was added dropwise, and stirred at room temperature for 2 hours. The obtained precipitate was washed with methanol and dried at 50° C. under reduced pressure for 3 hours to obtain a pale yellow solid monomer (di-2-naphthyl disulfide).
[0138] <Monomer Synthesis Example 4>
[0139] In a flask equipped with a stirrer, 16.0 g of sulfur and 497 mL of tetrahydrofuran were placed and stirred under an ice bath. Next, a solution prepared by dissolving 12.1 g of magnesium and 100 g of 1-bromo-2-methylnaphthalene in 452 mL of tetrahydrofuran was added dropwise under an ice bath, stirred for 1 hour, stirred at room temperature for 20 hours, and subjected to liquid separation treatment with a saturated aqueous ammonium chloride solution. The obtained organic layer was dehydrated with sodium sulfate, filtered, and the filtrate was evaporated to obtain 78.8 g of 2-methyl-1-naphthol.
[0140] Next, in a flask equipped with a stirrer, 78.8 g of the obtained 2-methyl-1-naphthol and 680 mL of chloroform were placed, and a solution of 57.4 g of iodine dissolved in 340 mL of methanol was added dropwise, and stirred at room temperature for 1 hour. Next, 1 M hydrochloric acid, 1 M sodium hydroxide aqueous solution, and brine were used for liquid separation in sequence, and the obtained organic layer was dehydrated with sodium sulfate, filtered, and the filtrate was evaporated to obtain a yellow oil. After dissolving the oil in 450 mL of chloroform, 900 mL of methanol was added to crystallize it, and the obtained solid was dried at 50° C. under reduced pressure for 3 hours to obtain a yellow solid monomer [bis(2-methylnaphthyl) disulfide].
[0141] [Manufacturing of polymers or copolymers]
[0142] <Polymer Synthesis Example 1>
[0143] In a flask equipped with a stirrer, 4.6 g (20 mmol) of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, 2.2 g (20 mmol) of trifluoroacetic acid, and 10 mL of chloroform were placed. After stirring, 7.6 g (20 mmol) of the monomer obtained in the above-mentioned monomer synthesis example 1 was added and stirred for 40 hours. Next, 20.6 g (180 mmol) of trifluoroacetic acid and 190 mL of chloroform were added to the reaction solution, and then stirred for 24 hours. After removing the precipitate by filtration, the filtrate was dripped into 2000 mL of stirred ethanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by dripping was recovered and washed with ethanol, methanol, 3% potassium hydroxide aqueous solution, and pure water in sequence. Next, the obtained precipitate was dissolved in 100 mL of chloroform again and dripped into 1000 mL of stirred methanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dropwise addition was recovered, washed with methanol, a 3% by mass aqueous potassium hydroxide solution, and pure water in that order, and then dried at 80° C. under reduced pressure to obtain 5.8 g of the polymer of the present invention [poly(2-methoxynaphthalene sulfide)] containing the structural unit represented by the above formula (1ca). The polystyrene-equivalent weight average molecular weight M of the obtained polymer was W is 1300.
[0144] <Polymer Synthesis Example 2>
[0145] In a flask equipped with a stirrer, 5.8 g of the polymer obtained in the above polymer synthesis example 1 and 75 mL of dichloromethane were placed under a nitrogen atmosphere, cooled to 0°C using an ice bath, and then 60 mL of a dichloromethane solution of boron tribromide (1 mol / L) was added dropwise, followed by stirring for 20 hours. Then, 60 mL of pure water was added dropwise to quench the reaction, and the precipitate was washed with dichloromethane and pure water, and then dried at 50°C under reduced pressure, thereby obtaining 3.6 g of the polymer of the present invention [poly(2-hydroxynaphthalene sulfide)] containing the structural unit represented by the above formula (1ba).
[0146] <Polymer Synthesis Example 3>
[0147] In a flask equipped with a stirrer, 4.6 g (20 mmol) of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, 0.8 g (7 mmol) of trifluoroacetic acid, and 7 mL of chloroform were placed. After stirring, 5.6 g (20 mmol) of the monomer obtained in the above-mentioned monomer synthesis example 2 was added and stirred for 40 hours. Next, 73 mL of chloroform was added to the reaction solution, and after removing the precipitate by filtration, the filtrate was dripped into 800 mL of stirred ethanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dripping was recovered, and after washing with ethanol, methanol, 3% by mass potassium hydroxide aqueous solution, and pure water in sequence, it was dissolved in 80 mL of chloroform again and dripped into 800 mL of stirred methanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dropwise addition was recovered, washed with methanol, a 3 mass % potassium hydroxide aqueous solution, and pure water in that order, and then dried at 80° C. under reduced pressure to obtain 4 g of a polymer [poly(2-methoxyphenylene sulfide)] containing a structural unit represented by the following formula. The polystyrene-equivalent weight average molecular weight of the obtained polymer was M: W is 3000.
[0148] [Chemistry 17]
[0149]
[0150] (In the formula, OMe represents a methoxy group.)
[0151] <Polymer Synthesis Example 4>
[0152] In a flask equipped with a stirrer, 4 g of the polymer obtained in the above polymer synthesis example 3 and 86 mL of dichloromethane were placed under a nitrogen atmosphere, cooled to 0°C using an ice bath, and then 86 mL of a dichloromethane solution of boron tribromide (1 mol / L) was added dropwise, and stirred for 18 hours. Then, 100 mL of pure water was added dropwise to quench the reaction, and the precipitate was washed with dichloromethane and pure water, and then dried at 50°C under reduced pressure to obtain 3.6 g of a polymer [poly(2-hydroxyphenylene sulfide)] containing a structural unit represented by the following formula.
[0153] [Chemistry 18]
[0154]
[0155] <Polymer Synthesis Example 5>
[0156] In a flask equipped with a stirrer, 4.6 g (20 mmol) of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, 2.2 g (20 mmol) of trifluoroacetic acid, and 20 mL of dichloromethane were placed, and after stirring, 2.8 g (10 mmol) of the monomer obtained in the above-mentioned monomer synthesis example 2 and 3.2 g (10 mmol) of the monomer obtained in the above-mentioned monomer synthesis example 3 were added, and stirred for 70 hours. Next, 60 mL of chloroform was added to the reaction solution, and after removing the precipitate by filtration, the filtrate was dripped into 800 mL of stirred ethanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dripping was recovered, and after washing with ethanol, methanol, 3% by mass potassium hydroxide aqueous solution, and pure water in sequence, it was dissolved in 80 mL of chloroform again, and dripped into 800 mL of stirred methanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dropwise addition was recovered, washed with methanol, a 3% by mass aqueous potassium hydroxide solution, and pure water in that order, and then dried at 80° C. under reduced pressure to obtain 3.0 g of the copolymer of the present invention [poly(2-naphthalene sulfide / 2-methoxyphenylene sulfide)] containing two structural units represented by the following formula. The polystyrene-equivalent weight average molecular weight M of the obtained copolymer was: W is 1300.
[0157] [Chemistry 19]
[0158]
[0159] (In the formula, OMe represents a methoxy group.)
[0160] <Polymer Synthesis Example 6>
[0161] In a flask equipped with a stirrer, 2.0 g of the copolymer obtained in the above Polymer Synthesis Example 5, 0.8 g of sodium hydroxide, 2.0 g of 1-dodecanethiol, and 14 mL of N-methyl-2-pyrrolidone were placed under a nitrogen atmosphere and stirred at 130° C. for 3 hours. Next, dilute hydrochloric acid was added to the reaction solution for neutralization, and the precipitate was washed with pure water and hexane and dried at 80° C. under reduced pressure to obtain 1.8 g of the copolymer of the present invention [poly(2-naphthalene sulfide / 2-hydroxyphenylene sulfide)] containing two structural units represented by the following formula.
[0162] [Chemistry 20]
[0163]
[0164] <Polymer Synthesis Example 7>
[0165] In a flask equipped with a stirrer, 4.6 g (20 mmol) of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, 2.2 g (20 mmol) of trifluoroacetic acid, and 20 mL of dichloromethane were placed, and after stirring, 2.8 g (10 mmol) of the monomer obtained in the above-mentioned monomer synthesis example 2 and 3.5 g (10 mmol) of the monomer obtained in the above-mentioned monomer synthesis example 4 were added, and stirred for 70 hours. Next, 60 mL of chloroform was added to the reaction solution, and after removing the precipitate by filtration, the filtrate was dripped into 800 mL of stirred ethanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dripping was recovered, and after washing with ethanol, methanol, 3% by mass potassium hydroxide aqueous solution, and pure water in sequence, it was dissolved in 80 mL of chloroform again, and dripped into 800 mL of stirred methanol / 12N hydrochloric acid = 95 / 5 (volume ratio). The precipitate generated by the dropwise addition was recovered, washed with methanol, a 3% by mass aqueous potassium hydroxide solution, and pure water in that order, and then dried at 80° C. under reduced pressure to obtain 2.0 g of the copolymer of the present invention [poly(2-methyl-1-naphthylene sulfide / 2-methoxyphenylene sulfide)] containing two structural units represented by the following formula. The polystyrene-equivalent weight average molecular weight M of the obtained copolymer was: W is 1700.
[0166] [Chemistry 21]
[0167]
[0168] (In the formula, Me represents a methyl group and OMe represents a methoxy group.)
[0169] <Polymer Synthesis Example 8>
[0170] In a flask equipped with a stirrer, 2.0 g of the polymer obtained in the above Polymer Synthesis Example 7, 0.8 g of sodium hydroxide, 2.0 g of 1-dodecanethiol, and 14 mL of N-methyl-2-pyrrolidone were placed under a nitrogen atmosphere and stirred at 130° C. for 3 hours. Next, dilute hydrochloric acid was added to the reaction solution for neutralization, and the precipitate was washed with pure water and hexane, and dried at 80° C. under reduced pressure to obtain 1.7 g of the copolymer of the present invention [poly(2-methyl-1-naphthylene sulfide / 2-hydroxyphenylene sulfide)] containing two structural units represented by the following formula.
[0171] [Chemistry 22]
[0172]
[0173] (In the formula, Me represents a methyl group.)
[0174] [Preparation of resin composition]
[0175] <Example 1>
[0176] 3.6 g of the polymer obtained in the above polymer synthesis example 2 as component (A), 19.7 g of cyclopentanone as component (B), 0.7 g of triglycidyl isocyanurate as component (C) (20 parts by mass relative to 100 parts by mass of component (A), and 0.001 g of R-40 (manufactured by DIC Corporation) as a surfactant were mixed to prepare a uniform solution. Then, the solution was filtered using a polyethylene microfilter having a pore size of 0.2 μm to obtain a resin composition (solid content concentration 18% by mass).
[0177] <Comparative Example 1>
[0178] A resin composition (solid content concentration: 18% by mass) was obtained by the same procedure as in Example 1 except that the polymer obtained in the above-mentioned Polymer Synthesis Example 4 was used as a polymer not belonging to the (A) component.
[0179] <Example 2>
[0180] A resin composition (solid content concentration: 18% by mass) was obtained by the same procedure as in Example 1 except that the copolymer obtained in the above-mentioned Polymer Synthesis Example 6 was used as the component (A).
[0181] <Example 3>
[0182] A resin composition (solid content concentration: 18% by mass) was obtained by the same procedure as in Example 1 except that the copolymer obtained in the above-mentioned Polymer Synthesis Example 8 was used as the component (A).
[0183] [Refractive index evaluation]
[0184] The resin compositions prepared in Examples 1 to 3 and Comparative Example 1 were respectively applied to a silicon wafer using a spin coater and baked on a hot plate at 100°C for 1 minute. Then, they were baked at 200°C for 5 minutes to form a resin film with a film thickness of 200 nm. For these resin films, the refractive index at a wavelength of 550 nm was measured using a spectroscopic ellipsometer M-2000 (manufactured by JA Woollam Japan (Strain)). The results are shown in Table 1.
[0185] [Dry Etching Rate Evaluation]
[0186] The resist solution THMR-iP1800 (manufactured by Tokyo Ohka Industry Co., Ltd.) was applied to a silicon wafer using a spin coater, and baked on a hot plate at 90°C for 1.5 minutes, at 110°C for 1.5 minutes, and further at 180°C for 1 minute to form a resist film with a film thickness of 1 μm. The resist film was dry-etched using a dry etching apparatus RIE-10NR (manufactured by Samco Co., Ltd.) (etching gas: CF4), and the dry etching rate of the resist film was measured. Next, the resin compositions prepared in Examples 1 to 3 and Comparative Example 1 were applied to a silicon wafer using a spin coater, and baked on a hot plate at 100°C for 1 minute. Then, the resin film with a film thickness of 1 μm was formed by baking at 200°C for 5 minutes, and the dry etching rate was measured in the same manner. Then, the dry etching rate of the resin film obtained from the resin composition prepared in Examples 1 to 3 and Comparative Example 1 relative to the above-mentioned resist film was calculated. The results are shown in Table 1.
[0187] [Evaluation of lens formability]
[0188] The resin compositions prepared in Examples 1 to 3 and Comparative Example 1 were respectively coated on a silicon wafer using a spin coater and baked on a hot plate at 100°C for 1 minute. Then, it was baked at 200°C for 5 minutes to form a resin film with a film thickness of 1.2 μm. Next, the resist solution THMR-iP1800 (manufactured by Tokyo Ohka Industry Co., Ltd.) was coated on the resin film using a spin coater and baked on a hot plate at 90°C for 1.5 minutes. Then, an i-ray stepper (NSR-2205i 12D, NA=0.63, manufactured by Nikon Co., Ltd.) was used to expose through a mask forming a square dot pattern of 1 μm×1 μm, and after baking at 110°C for 1.5 minutes, it was developed using a 2.38% by mass concentration of tetramethylammonium hydroxide (TMAH) aqueous solution. Furthermore, it was baked at 180°C for 1 minute to form a lens pattern on the above-mentioned resin film, and the width of the lens pattern was measured. Then, using a dry etching apparatus 2300 Versys (registered trademark) Kiyo (registered trademark) 45 (manufactured by Lam Research Co., Ltd.) (etching gas: CHF3), the resin film was dry-etched using the lens pattern as an etching mask until the lens pattern disappeared, and the width of the formed microlens was measured.
[0189] When the width of the microlens after dry etching was greater than or equal to the width of the lens pattern before dry etching, the lens moldability was evaluated as "○", and when the width of the microlens after dry etching was smaller than the width of the lens pattern before dry etching, the lens moldability was evaluated as "×".
[0190] [Table 1]
[0191]
[0192] It was confirmed that the resin film obtained from the resin composition containing the polynaphthalene sulfide resin of the present invention has a high refractive index of 1.75 or more at a wavelength of 550 nm and exhibits excellent lens moldability in an etch-back method.
[0193] From the above results, it is understood that the polymer and the resin composition for optical lens of the present invention can be used for optical lenses, particularly microlenses.
Claims
1. A polymer comprising a structural unit represented by the following formula (1), wherein: The structural unit does not include a structural unit represented by the following formula (1a), [Chemistry 1] In the formula, X independently represents a methyl group, an ethyl group, a methoxy group, an ethoxy group or a hydroxyl group, and n represents an integer of 1 to 6. [Chemistry 2] 2. The polymer according to claim 1, wherein In the structural unit represented by the formula (1), n represents 1.
3. The polymer according to claim 1 or 2, wherein In the structural unit represented by the formula (1), X represents a methyl group or an ethyl group.
4. The polymer according to claim 1 or 2, wherein In the structural unit represented by the formula (1), X represents a methoxy group or an ethoxy group.
5. The polymer according to claim 1 or 2, wherein In the structural unit represented by the formula (1), X represents a hydroxyl group.
6. The method for producing a polymer according to claim 1 or 2, which is a method for producing a polymer comprising the structural unit represented by the formula (1), the method comprising: A step of oxidatively polymerizing a disulfide monomer represented by the following formula (2) and / or a thiol monomer represented by the following formula (3), wherein the disulfide monomer does not include a disulfide monomer represented by the following formula (2a), and the thiol monomer does not include a thiol monomer represented by the following formula (3a), [Chemistry 3] In the formula, X and n have the same definitions as in formula (1), [Chemistry 4] 7. A resin composition for an optical lens, comprising: (A) a polymer according to claim 1 or 2 and / or a polymer comprising a structural unit represented by the following formula (4) and (B) an organic solvent, [Chemistry 5] 8. The resin composition for an optical lens according to claim 7, wherein The (B) component contains at least one organic solvent selected from the following: ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, ethyl lactate, n-butyl lactate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, 2-heptanone, cyclopentanone, cyclohexanone, γ-butyrolactone, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. 9 . The resin composition for an optical lens according to claim 7 , further comprising (C) a polyfunctional epoxy compound. 10 . The resin composition for an optical lens according to claim 7 , which is used for producing a microlens. 11 . A microlens obtained from the resin composition for an optical lens according to claim 10 .
Citation Information
Patent Citations
Method of treating successive signal samples and digital filter for carrying out the method
EP0014151A1
Manufacture of solid-state image sensing device
JP1989010666A
On-chip lens and manufacture thereof
JP1994112459A
Molding material and optical member using the same
JP2015168790A
Molding material and method for producing the same, and optical member and method for producing the same
JP2017052834A